The Effect of The Multimedia-Assisted Problem-Based Learning Model on Student Learning Motivation - Laili Atil Far'i; Muh. Fahrurrozi; Marhamah Marhamah (IJE : Interdisciplinary Journal of Education, 2023)
This study aimed to determine the multimedia-assisted problem-based learning model's effect on motivation in mathematics studies learning. This quasi-experiment study used a nonequivalent control group pretest-posttest design. The study sample was all grade students at SD Negeri 4 Pringgabaya, which comprised 60 students and two classes using a non-probability sampling. To collect data using questionnaires. The experimental results show that the multimedia-assisted problem-based learning model positively impacts motivation in mathematics studies learning. This indicates that the pretest average in the experimental class is 43.33, while the post-test average is 76.50. The average pretest score in the control class was 47.80, while the average post-test was 69.33. Based on the T-Test analysis, the significance value obtained from the process results is 0.009 < 0.05, so Ho is rejected and Ha is accepted. Based on the n-gain test, the increase in student learning motivation in the experimental class is in the quite effective category with a value of 60%, while the increase in student learning outcomes in the control class is in the ineffective category, namely 39 %. So that, motivation Study students who are taught using a problem-based learning model assisted by multimedia are sufficient effective in increase motivation Study Mathematics students.